Temperature-sensitive virus derived from BHK cells persistently infected with HVJ (Sendai virus). - Kimura, Y (1975)
BHK-HVJ cells, a cell line of baby hamster kidney cells persistantly infected with HVJ (Sendai virus), started to produce infectious virus by shifting down the incubation temperature from 38 to 32 C. The virus derived from BHK-HVJ cells, designated as HJV-pB, was effectively neutralized with antibody against wild-type virus (HVJ-W) which was used for the establishment of BHK-HVJ cells. HVJ-pB replicated in eggs at 32 C, but not at 38 C, while HVJ-W grew equally well at both temperatures. When BHK cells infected with HVJ-PB were incubated at 38 C, production of infectious virus, hemagglutinin, and neuraminidase was markedly restrained, whereas a considerable amount of viral nucleocapisid and envelope antigens was detected in the cells by complement fixation tests. These viral activities became detectable immediately after temperature shift-down from 38 to 32 C even at the later stage of infection. HVJ-pB was indistinguishable from HJV-W with respect to particle size, density, and morphological characteristics, but appeared to possess a higher neuraminidase activity and was inactivated more rapidly at 50 C than HVJ-W. HVJ-pB was less cytocidal and could easily cause latent infection in BHK and mouse L cells.